Electro-gene therapy followed by intratumoral injection of pcDNA3.1-p27Kip1 wild type in human tongue base cancer cells SP-C3 xenograft - Supriatno, S.; Sasmita, Inne Suherna (Padjadjaran Journal of Dentistry, 2009)
Human tongue base cancers are characterized by a high degree of local invasion and metastasis to the regional lymph nodes and included a disease with difficult treatment. A novel method for high-efficiency and region-controlled in vivo gene transfer was developed by combining electro-gene therapy and plasmid (pcDNA). The aims of the study were to examine the efficiency of transfection of p27Kip1 gene by electro-gene therapy and to evaluate p27Kip1 gene therapy in Supriâs clone-3 (SP-C3) xenografts using pcDNA3.1-p27Kip1 wild-type (wt) and pcDNA3.1 empty vector (neo) with electro-gene therapy. To investigate gene transfer method, the enhanced green fluorescence protein (EGFP) gene was transfected into xenografts by electro-gene therapy. The efficiency of p27Kip1 gene transfection at protein level was confirmed by Western blotting. To estimate the reduction in tumour size in Wistar Balb/c mice after electro-gene therapy with p27Kip1 wt gene was examined by tumorigenesis assay. To evaluate the induction of apoptosis was carried out by colourimetric assay. The result, the growth of tumours was markedly suppressed by p27Kip1 wt gene transfection. Up-regulation of p27Kip1 protein was detected in pcDNA3.1-p27Kip1 wt. Apoptosis induction through the activity of caspase -3 and -9 was significantly increased in p27Kip1 wt-transfected tumours. These results suggest that it is possible to transfer p27Kip1 wt into tongue base cancer cell xenografts using electro-gene therapy. p27Kip1 wt had a high-potential to suppress the growth of tumours. Conclusion, electro-gene therapy followed by intratumoral injection of pcDNA3.1-p27Kip1 wt had a high-potential to suppress the growth of a human tongue base cancer cell xenograft.